Co-designing a film showcasing the dental experiences of community returners (ex-offenders) - Booth, Joelle; McMullen, Heather; Rodriguez, Andrea; Muirhead, Vanessa (Frontiers in Oral Health, 2025)
BackgroundThe oral health of over 90,000 individuals in UK prisons is four times worse than the general population. A recent scoping review on the oral health of prisoners inside the justice system highlighted the lack of research about what happens when they transition out of prison to become community returners.ObjectivesTo co-design a film to showcase the dental experiences of community returners before and after they transition out of prison, change perceptions and inform oral health research priorities.MethodsThis action research involved five community returners, recruited through third sector organisations, who attended virtual workshops. Participants in the first workshop designed the storyboard; community returners incorporated their own stories into fictional characters to portray their lived experiences. They developed the character stories and wrote the script in the second workshop. A community film production company produced the film and used professional actors who had contact with the justice system to depict the characters in the film.ResultsThe final film, titled “My Story, My Words, My Mouth” explored themes such as self-care oral health behaviours, dental care provision in prison, access to healthcare, stigmatisation, disclosure and improving oral health to support societal reintegration. The film was screened at an open event for stakeholders and included a question-and-answer session and recorded videos where viewers shared their feedback to inform future research projects.ConclusionCo-design can be an empowering platform to hear the voices of community returners. Using the medium of film an oral health promotion tool can build understanding about the oral health needs of underrepresented groups. This egalitarian and power-sharing approach can also provoke critical discussion and actively involve underrepresented people in research that impacts their lives to develop strategies, to set priorities and improve their oral health.